Penerapan Alat Pemotong Dodol Mangrove Pidada pada Kelompok Industri Rumah Tangga di Kecamatan Muara Gembong - Martana, Budhi; Sembiring, Rosali Colia; Wijayanti, Sri Hapsari; Mahmud, Muhammad Alfayad; Rianto, Ridwan Bambang (Institute for Research and Community Services, 2024)
Pidada mangrove trees grow in the beach Bahagia Village area, Muaragembong District, Bekasi Regency, West Java. The potential of pidada fruit has been widely utilized by community members in Muaragembong into processed food products of various healthy foods and drinks. One type of food that is widely produced by the local community is mangrove pidada dodol. The Senturi group in Kampung Beting, Pantai Bahagia Village since 2016 has produced pidada mangrove dodol, but the processing is still done conventionally using a kitchen knife and wooden ruler, so that the cut results show an uneven shape including thickness and the cutting process takes quite a long time. The purpose of this community service activity is to improve the quality of pidada mangrove dodol through the application of appropriate technology for pidada mangrove dodol cutting machine using an electric motor drive system and rotary knife type. The activities that took place from June to September 2024 were divided into four stages, namely field surveys, making cutting machines, training in the use of cutting machines, and mentoring and evaluation. The Senturi group was trained in the use of the cutting machine and had hands-on experience with the machine. The results of the implementation of the cutting machine are able to improve the cutting process of dodol dough with a time of 90 seconds and produce dodol pidada pieces with a size of 18x18 mm with a production capacity of 42 kg/hour, and the pieces have uniform dimensions and sizes; thus the use of this cutting machine has an impact on the household industry.